Wednesday

July 23, 2014

July 23, 2014

Posted by **Angie** on Tuesday, December 20, 2011 at 5:16pm.

- math/calculus -
**Steve**, Tuesday, December 20, 2011 at 6:29pmNote that x^2 - 2x + 1 = (x-1)^2

f(x) = (x-1)^2/3

f' = 2/3 (x-1)^-1/3

f'' = -2/9 (x-1)^-4/3

**Related Questions**

Calculus - Find the functions a) f o g, b) g o f, c) f o f, d) g o g, and their ...

Calc - Find the functions a) f o g, b) g o f, c) f o f, d) g o g, and their ...

Algebra - Could you please help me with some math problems? Thanks! Add or ...

Calculus-Solved-Please Check? - estimate cube root of 25 by linear approximation...

Calculus - Express the function in the form f o g. G(x)= The cube root of (x/1+x...

Algebra - Simplify: 5(cube root of 16) + 2(cube root of 54) 5 times the cube ...

AP Calculus - If the linearization of y= cube root of x at x=64 is used to ...

Math PLEASE HELP ASAP - -PLEASE INCLUDE SOLUTIONS AND EXPLAIN HOW YOU DID IT ...

calculus - Find the solution to the differential equation dy/dx = (x^3)/(y^2), ...

Math - i see were u got that from but this 1 is confusing. 6 (index 3) square ...